Clinical significance of hepatitis B virion and SVP productivity: relationships between intrahepatic and serum markers in chronic hepatitis B patients. Issue 2 (1st April 2014) - Lesmana, Cosmas Rinaldi Adithya; Jackson, Kathy; Lim, Seng Gee; Sulaiman, Ali; Pakasi, Levina S; Gani, Rino A; Hasan, Irsan; Sulaiman, Andri Sanityoso; Lesmana, Laurentius A; Hammond, Rachel; Revill, Peter; Locarnini, Stephen; et al.
Abstract : Background: Clinical use of hepatitis B viral (HBV) quantitative seromarker\s remains questionable since it is not precisely known whether they represent intrahepatic viral replication. Covalently closed circular DNA (cccDNA), relaxed circular DNA (rcDNA), and pregenomic RNA (pgRNA) are more likely to represent active HBV replication and their measurement can be used to derive virion productivity (VP; rcDNA/cccDNA), subviral particle (SVP) productivity (quantitative HBsAg/cccDNA), and replicative activity (RA; pgRNA/cccDNA). These can be used to compare relative HBV replication between HBeAg‐negative and ‐positive patients. Objective: To study the clinical significance of intrahepatic HBV replication phenomenon between HBeAg‐negative and ‐positive patients and its correlation with quantitative HBV seromarkers. Method: This was a prospective study between January 2010 and December 2011. Study subjects were naive chronic hepatitis B patients from Cipto Mangunkusumo and Medistra Hospitals. All patient samples underwent liver biochemistry and HBV seromarkers testing (HBeAg, quantitative HBsAg and HBV DNA levels), and patients underwent liver biopsy. Stored liver specimens were analysed for intrahepatic rcDNA, cccDNA, and pgRNA with quantification performed by real‐time PCR. Comparison of HBV markers between HBsAg‐positive and ‐negative patients was carried out using the Mann–Whitney U‐test. Pearson's correlation test was performed among HBV intrahepatic and seromarkers using their log‐transformed values. Results: A total of 104 patients were enrolled in this study; 54 (51.9%) were male. Patients' mean age was 41.9 ± 11.63 years (range 19–70 years). Sixty‐one patients (58.7%) were HBeAg‐negative. All HBV markers were significantly higher in HBeAg‐positive than HBeAg‐negative patients, except for SVP productivity and RA. Serum HBV DNA was strongly correlated with intrahepatic total HBV DNA ( r  = 0.771), cccDNA ( r  = 0.774), and rcDNA ( r  = 0.780) while serum quantitative HBsAg showed only moderate correlation with intrahepatic total DNA ( r  = 0.671), cccDNA ( r  = 0.632), rcDNA ( r  = 0.675), and SVP productivity ( r  = 0.557). Conclusions: Serum HBV DNA concentration and quantitative HBsAg might not accurately predict intrahepatic viral activity. Virion and SVP production do not occur in parallel with replicative activity.